Synthesis, characterization and biological activities of dithiocarbazate nitrogen sulfur donor ligands and their metal complexes - Elhassan, Hiba Hayder Hanza (2012)
Three new Schiff bases were synthesized from the condensation reaction of S-benzyldithiocarbazate (SBDTC) with acetylferrocene, and S-4-methylbenzyldithiocarbazate (S4MBDTC) with S-camphorquinone and R-camphorquinone. A series of fifteen metal complexes were successfully synthesized from the reaction of the Schiff bases with metal salts of Cobalt(II), Nickel(II), Cadmium(II), Copper(II), and Zinc(II). All the compounds were characterized using various physio-chemical and spectroscopic techniques. Two structures were determined using X-ray diffraction analysis. The crystal structure of Ni(II) complex of camphorquinone and S-4-methylbenzyldithiocarbazate showed that the complex exhibited a six coordinate octahedral geometry. The Schiff base acted as a uninegatively charged tridentate ligand coordinating to the Ni(II) ion via the azomethine nitrogen atom, thiolate sulfur atom, and carbonyl oxygen atom. Unfortunately, attempts to grow crystals of the other metal complexes were not successful. These newly synthesized compounds exhibited significant cytotoxic activities towards MCF-7 (Human breast carcinoma cells with positive estrogen receptors) and MDA-MB-231 (Human breast carcinoma cells with negative estrogen receptors). Schiff bases were found to be more active towards the tested cancer cells than their metal complexes.